Teoria pomiaru łącznego w pomiarze preferencji konsumentów - Rybicka, Aneta (Conjoint Measurement Theory in Consumers' Preference Measurement, 2006)
In measurement of stated preference we used decompositional methods: conjoint analysis and discrete choice methods. In the paper conjoint analysis methods, their theoretical basis - conjoint measurement - and research procedure are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 50-61